Towards Understanding the Relationship Between ER Stress and Unfolded Protein Response in Amyotrophic Lateral Sclerosis - Zhao, Chenxuan; Liao, Yong; Rahaman, Abdul; Kumar, Vijay (Frontiers in Aging Neuroscience, 2022)
Biological stress due to the aberrant buildup of misfolded/unfolded proteins in the endoplasmic reticulum (ER) is considered a key reason behind many human neurodegenerative diseases. Cells adapted to ER stress through the activation of an integrated signal transduction pathway known as the unfolded protein response (UPR). Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease characterized by degeneration of the motor system. It has largely been known that ER stress plays an important role in the pathogenesis of ALS through the dysregulation of proteostasis. Moreover, accumulating evidence indicates that ER stress and UPR are important players in TDP-43 pathology. In this mini-review, the complex interplay between ER stress and the UPR in ALS and TDP-43 pathology will be explored by taking into account the studies from in vitro and in vivo models of ALS. We also discuss therapeutic strategies to control levels of ER stress and UPR signaling components that have contrasting effects on ALS pathogenesis.